Insights into the properties and role of Mangifera indica (Mango) peel in decontamination of wastewater - Smruti Rekha Patra; Sneha Prabha Mishra (Sustainable Environment)
Wastewater coming out of industries contains heavy metal ions and dyes, which are harmful to the environment. Therefore, their removal is essential before they are released into common water bodies. Adsorption is a low-cost method of pollutant removal. Adsorption becomes more cost-effective when inexpensive materials are used. Mangifera indica (Mango) is a popular fruit, and its peel is a significant waste in food processing industries. It can be used in either unmodified, physically, chemically, or thermally activated forms for the removal of dyes and heavy metal ions present in water. The modified form of mango peel (MP) is more efficient than the unmodified forms. The surface characterization (XRD, FTIR, SEM, TGA, PZC, proximate analysis, particle size distribution, BET surface area) of MP and its various forms has been thoroughly reviewed to know their surface properties. Among the dyes, MB removal was highest, i.e. 6352.22 mg/g on H3PO4 modified MP. Similarly, among the heavy metal ions, Mn2+ removal was highest, i.e. 403.23 mg/g on the MP-derived activated carbon-Ni composite. MP and its various forms contain Ca2+, Mg2+, K+ and Na+, which can easily be exchanged with positive pollutants present in H2O. The interaction of pollutants with MP and its various derivatives is mainly due to ion exchange, electrostatic attraction, complexation through π electrons, pore filling and precipitation. For regeneration and reuse of the materials, till now researchers have used HCl as the desorbing agent for both dyes and metal ions. The materials can be reused for a maximum up to 5 adsorption-desorption cycles.